Dredging in coastal waters [editor] D. Eisma - Eisma, D (Taylor & Francis, 2006)
The varied use of dredgers has led to the development of a variety of dredger types, from small ones appropriate to modest inshore projects, to very large sea-going dredgers for large-scale projects calling for the storage of dredged material within the ship. This book, which is the first book dedicated to dredging and its environmental impact in the widest sense, contains chapters on dredging operations in the Netherlands, Belgium, the UK, Spain, the US, China and Singapore. Additional chapters discuss more general aspects such as dredging techniques, monitoring of dredging operations, and the prospects of dredging in a changing environment. As well as providing information on dredging activities in different areas, it gives an insight into the activities and problems (environmental or other) involved in modern dredging